Evaluación de la calidad de un servicio de voluntariado en oncología: un Análisis Importancia-Valoración (IPA) - Gil Calzada, Luis; Carrasco Estévez, Ainhoa; Muñoz Garzón, Víctor Manuel (Psicooncología, 2016)
Objective: Using an Importance-Performance Analysis (IPA), this paper examined a Radiotherapy and Oncological Patient and Non-patient perceived importance and performance of ten Humanization Volunteer Program selection factors in the General Hospital in Spain. Methods: The authors identified a list of seven items from the Health-marketing literature reviews, and each item was rated using a 5-point Likert scale. Responses were obtained of 148 usable interviews. Results: The importance-performance patient grid was corrected with literature recommendations and, in the patient sample, shows three items fall in the “Keep up the good work” quadrant, four items fall into the “Low priority” quadrant, zero items fall into the “Possible overkill” quadrant, and no items fall in the “Concentrate here” quadrant. Non-patient (n=80) factors means shows statistical differences with patient (n=68) means in catering (t=-2.38; df.=146; p<0.05), and information (t=2.16; df146; p<0,05). Conclusions: The results are useful in identifying areas for strategic focus to help Health Services managers develop humanization programs with volunteer workers and different program users. Implication to volunteer programs managers and researchers were discussed.